Diversity of practices in social dialogue in the public service in selected African countries - Mpfariseni Budeli; Theodore Kasongo Kamwimbi (International Labour Organization (ILO), 2022)
Social dialogue, which forms part of the regulation of labour relations in the public sector, can take a variety of forms ranging from the simple act of publishing informal recommendations, or consultation and sharing information to the most formal and binding negotiated agreements, bargaining or more developed forms of consultation. Although each country has its own cultural, historical, economic, and political setting, there is a diversity of practices in social dialogue in the public service, and the common model of social dialogue for all countries seems to be freedom of association and the right to collective bargaining. It is, therefore, worth showing how different countries manage to adapt their diverse practices in social dialogue in the public service to the national situation. To this end, this report focuses on five selected African countries, namely Angola, Kenya, Tunisia, South Africa, and Ghana. These countries represent respectively the five main subregions of Africa (Central, Eastern, Northern, Southern and Western Africa) as suggested by the ILO. A thorough analysis of these countries' social dialogue mechanisms in the public service shows that the functioning and sustainability of such mechanisms may be facilitated by permanent structures or institutions, such as national tripartite consultative committees.
Keywords: 330; social dialogue; public sector